Activation of group I metabotropic glutamate receptors induces long-term depression at sensory synapses in superficial spinal dorsal horn - Chen, Jianguo; Heinke, Bernhard; Sandkühler, Jürgen (Neuropharmacology, 2000)
Low-frequency stimulation of primary afferent Aδ-fibers can induce long-term depression of synaptic transmission in rat superficial spinal dorsal horn. Here, we have identified another form of long-term depression in superficial spinal dorsal horn neurons that is induced by specific group I but not group II metabotropic glutamate receptor (mGluR) agonists. Synaptic strength between Aδ-fibers and dorsal horn neurons was examined by intracellular recordings in a spinal cord-dorsal root slice preparation from young rat. In the presence of bicuculline and strychnine, bath application of (1S,3R)-1-aminocyclopentane-1,3-dicarboxylic acid ((1S,3R)-ACPD) or the specific group I mGluR agonist (S)-3,5-dihydroxyphenylglycine ((S)-3,5-DHPG) but not the specific group II mGluR agonist (2S,2′R,3′R)-2-(2′,3′-dicarboxycyclopropyl)glycine (DCG-IV) for 20 min produced an acute and a long-term depression of synaptic strength. Bath application of the N-methyl-d-aspartate receptor antagonist d-2-amino-5-phosphonovaleric acid did not affect these depressions by (1S,3R)-ACPD. After pre-incubation of slices with pertussis toxin, a G-protein inhibitor, (1S,3R)-ACPD still induced acute and long-term depressions. The phospholipase C inhibitor U73122 stereoselectively blocked the induction of long-term depression without affecting acute synaptic inhibition. This study demonstrates that, in the spinal cord, direct activation of group I mGluRs that are coupled to phospholipase C through pertussis toxin-insensitive G-proteins induces a long-term depression of synaptic strength. This may be relevant to the processing of sensory information in the spinal cord, including nociception.
Gesehen am 03.05.2021